The Impact of Specific Knowledge on Death Penalty Opposition: An Empirical Test of the Marshall Hypothesis - Harmon, Talia Roitberg (Crime & delinquency, 2022)
As we approach the 50-year anniversary of the landmark Furman decision, the time is ripe for a renewed empirical test of the hypotheses Justice Marshall presented in his concurring opinion. Most relevant to this study, he suggested in his second proposition that ?people who were fully informed as to the purposes of the penalty and its liabilities would find the penalty, shocking, unjust and unacceptable.? While there has been much empirical testing of this hypothesis, the intent of this study is to add to the existing literature by examining whether specific types of information about capital punishment is associated with opposition to capital punishment. Data were collected by an instructor who taught death penalty classes (n?=?122 subjects) to test this hypothesis. Results provide qualified support for Marshall?s second hypothesis that knowledge is significantly related to an increase in death penalty opposition. Moreover, the following factors were significant predictors of overall change in participants? opinion: cost, deterrence, race of victim, and evolving societies. Surprisingly, the innocence items did not appear statistically significant in altering opinions. Future research should continue to explore further aspects of the Marshall hypothesis such as the effect of different methods of information delivery.